2008 Solisti Carolina Poster - (:unkn) unknown (My University, 2018)
Featuring focal points from the 2007-2008 season of the Artists Series.
A poster promoting the Nov. 15, 2008 performance of student chamber orchestra Solisti Carolina under the direction of Jeanette Sorrell of Apollo's Fire and a 1986 Wake Forest University alum.
Keywords: Performing arts